Das Polenbild im "Gelübde" von E. T. A. Hoffmann - Połczyńska, Edyta (Studia Germanica Posnaniensia, 2018)
The article is an analysis of E. T. A. Hoffmann's (1776-1822) short story entitled The vows (1817) conducted from the angle of occurrence of a Polish motive in it, connected with the Kościuszko Uprising. It is known from E. T. A. Hoffmann's biography that he was one of the not too numerous great Germans who had more extensive contacts with Poland. Experiences and news about Poland when E. T. A. Hoffmann married to a Polish woman from Poznań, Michalina Rohrer-Trzcińska collected during his stay in Poznań (1800-1802), Płock (1802-1804) and Warsaw (1804-1807) were reflected in his reviews, correspondence and artistic creation, specifically in two short stories The vows and Othello.